Lignin-based hard carbon material with high platform capacity, preparation of lignin-based hard carbon material and application of lignin-based hard carbon material in sodium-ion battery
By adsorbing zinc salts in lignin to generate in situ zinc templates, the problem of low platform capacity of hard carbon materials in sodium ion batteries is solved, and the combination of high platform capacity and environmentally friendly processes is achieved, which improves the energy density and cycle stability of the battery.
Patent Information
- Application Number
- CN202411846799.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The prior art is difficult to effectively increase the platform capacity of hard char material in sodium ion batteries, while taking into account low cost, simple process and environmental protection requirements.
By adsorbing zinc salts by lignin, the in-situ zinc template is generated, and the closed-pore structure of hard carbon is regulated, thereby increasing its platform capacity. This method does not require additional acid and alkali solvent removal templates, and the process is simple and environmentally friendly.
The high platform capacity of lignin-based hard charcoal materials is achieved, which improves its energy density and cycle stability in sodium ion batteries, while reducing production costs and process complexity.
Smart Images

Figure BDA0005189432420000141 
Figure HDA0005189432430000011 
Figure HDA0005189432430000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a high-platform capacity lignin-based hard carbon material, a preparation method thereof, and an application thereof in sodium ion batteries. Background Art
[0002] Due to the increasing demand for lithium resources and the scarcity of natural resources, lithium-ion batteries are in short supply in the market. Sodium ions have similar properties to lithium ions, and sodium has the advantages of abundant resources, wide distribution and low cost, making sodium-ion batteries the most promising supplement to lithium-ion batteries.
[0003] The negative electrode materials of sodium ion batteries include alloys, metal oxides and carbon-based materials. Among them, hard carbon in carbon-based materials has a high reversible specific capacity (~300 mAh g -1 ), low platform potential and long cycle life, which makes hard carbon have great potential in the practical application of sodium ion batteries.
[0004] Hard carbon refers to carbon materials that are difficult to graphitize even when carbonized at a high temperature of 2500°C. It is composed of curved graphene sheets and amorphous carbon structures. It is generally believed that the sodium storage mechanism of hard carbon is divided into two parts. The capacity in the slope zone above 0.1V comes from the intercalation of sodium ions in the graphite domain and adsorption on defects, while the capacity in the platform zone below 0.1V comes from the filling of sodium clusters in closed pores. The high platform capacity (<0.1V) in sodium-ion batteries has significant application advantages in improving energy density, fast charge and discharge performance, cycle stability and optimizing energy storage efficiency.
[0005] How to increase the closed-cell pore volume of hard carbon becomes the key to increasing the platform capacity. The template method is an effective way to construct a closed-cell structure by adjusting the size of the template to control the pore size and distribution inside the carbon material. Chinese patent application CN118684227A discloses a method for preparing a negative electrode material for a sodium ion battery. The patent uses ZnO as an activator and physically mixes it with coal powder for ball milling to obtain a mixture, and then carbonizes the mixture at high temperature to prepare a ZnO-activated pore-forming lignin-based hard carbon material. The hard carbon material prepared by this method has a capacity of 351mAh g -1 However, during the ball milling process, ZnO and coal powder are easily introduced with oxygen-containing functional groups. At the same time, the directly added nano ZnO will cause significant etching of the carbon material due to its large size, thereby generating a larger specific surface area, resulting in an increase in the slope capacity. The platform capacity is only 175 mAh g -1 Up to 210mAh g -1 , which is not conducive to the improvement of platform capacity.
[0006] The strategies for constructing closed pores in existing technologies often involve two or more cumbersome steps, and the removal process of hard templates and certain activators requires the use of solvents such as hydrochloric acid, sulfuric acid and hydrofluoric acid, which makes it difficult to take into account industrial production indicators such as low cost, simple process and environmental friendliness. In addition, the use of metal ions in precursor molecules as template sources is prone to template particle agglomeration and growth, resulting in excessively large and unevenly distributed template pores, while the addition of fixed-size templates often involves multiple steps, which can easily introduce defect sites and increase unnecessary specific surface area, making it impossible to obtain hard carbon materials with high platform capacity. It can be seen that the introduction method, size and dispersion degree of the template play a key role in regulating the closed-pore structure of hard carbon and obtaining hard carbon materials with high platform capacity.
[0007] Therefore, it is necessary to develop a preparation method that has no impact on the introduction of the template, uniform template size, high dispersion, low cost of precursor raw materials, simple process and environmental protection. Summary of the invention
[0008] The existing hard carbon material preparation has a low platform capacity ratio, and the preparation method for improving the platform capacity of hard carbon is difficult to take into account important industrialization indicators such as controllable pore structure of carbon materials, low cost, simple preparation route and green environmental protection. The primary purpose of the present invention is to provide a preparation method of high platform capacity lignin-based hard carbon material, specifically, lignin adsorbs zinc salt to generate in-situ zinc template pore formation to regulate the closed-pore structure of hard carbon.
[0009] The present invention utilizes the rich oxygen-containing functional groups of lignin to adsorb zinc ions, and zinc is evenly dispersed in the lignin molecules in an atomic manner. The uniform distribution of zinc and the utilization of the three-dimensional network structure of lignin inhibit the agglomeration growth of the generated ZnO, thereby ensuring that the nano ZnO used as a template has a uniform size and can be highly dispersed in the carbon material, thereby preparing a carbon material with a high specific surface area and a uniform pore structure, and converting the open pores into a closed pore structure under high-temperature carbonization, thereby increasing the closed pore volume of the material, and making the prepared lignin-based hard carbon material have an extremely high platform capacity.
[0010] Another object of the present invention is to provide a high platform capacity lignin-based hard carbon material prepared by the above preparation method.
[0011] Another object of the present invention is to provide the use of the above-mentioned high platform capacity lignin-based hard carbon material as a negative electrode material for sodium ion batteries.
[0012] The purpose of the present invention is achieved through the following technical solutions:
[0013] A method for preparing a high platform capacity lignin-based hard carbon material comprises the following steps:
[0014] (1) dispersing lignin in a zinc salt aqueous solution, heating and stirring, filtering, and drying to obtain a lignin-adsorbed zinc salt precursor;
[0015] (2) In an inert gas atmosphere, the precursor is carbonized in one step to obtain a lignin-based hard carbon material.
[0016] Preferably, in the zinc salt aqueous solution of step (1), the zinc salt is at least one of zinc acetate and zinc gluconate.
[0017] Preferably, the mass concentration of the zinc salt aqueous solution in step (1) is 5 to 20 g / L; more preferably 10 g / L.
[0018] Preferably, the mass ratio of lignin to zinc salt in step (1) is 12:1 to 4:1; more preferably 6:1.
[0019] Preferably, the heating and stirring in step (1) is carried out at a temperature of 50 to 100° C. for 0.5 to 24 h; more preferably, the heating and stirring is carried out at a temperature of 70° C. for 1 to 16 h; and most preferably, the heating and stirring is carried out for 1 to 4 h.
[0020] Preferably, the mass ratio of the lignin to the adsorbed zinc salt in step (1) is 30:1 to 10:1; more preferably 17:1 to 10:1; most preferably 17:1 to 12.5:1.
[0021] Preferably, the heating rate of the one-step carbonization in step (2) is 1 to 30°C / min, and the flow rate of the inert gas is 2 to 100 mL / min; more preferably, the heating rate of the one-step carbonization is 5°C / min, and the flow rate of the inert gas is 50 mL / min.
[0022] Preferably, the temperature of the one-step carbonization in step (2) is 1200-1700°C, and the time is 1-4 hours; more preferably, the temperature of the one-step carbonization is 1200-1600°C, and the time is 4 hours; most preferably, the temperature of the one-step carbonization is 1400-1600°C.
[0023] Preferably, the inert gas in step (2) is at least one of nitrogen, argon and helium.
[0024] Preferably, the lignin in step (1) is at least one of alkali wood lignin, enzymatic lignin and lignin sulfonate; the enzymatic lignin is the enzymatic lignin residue obtained in the biorefining process; the alkali lignin is the alkali lignin extracted from papermaking black liquor; and the lignin sulfonate is the lignin sulfonate extracted from sulfite pulping liquor.
[0025] Preferably, the drying temperature in step (1) is 80-100° C. and the drying time is 12-36 hours.
[0026] The high platform capacity lignin-based hard carbon material prepared by the above preparation method.
[0027] The above-mentioned high platform capacity lignin-based hard carbon material is used in sodium ion batteries.
[0028] The high-platform-capacity lignin-based hard carbon material of the present invention is used to prepare a negative electrode for a sodium ion battery: lignin-based hard carbon material (active material), acetylene black conductive agent, and polyvinylidene fluoride (PVDF) binder are weighed in a mass ratio of 8:1:1 respectively, PVDF is dissolved in an appropriate amount of 1-methyl-2-pyrrolidone (NMP), and stirred until completely dissolved, and then the evenly ground active material and acetylene black are added to the above solution, and stirring is continued to ensure that the slurry is evenly mixed; then the slurry is evenly coated on a round copper foil (diameter 12 mm), dried in a vacuum oven at 100° C., and finally flattened on a tablet press at a pressure of 10 MPa to obtain an electrode sheet.
[0029] The prepared electrode sheet, sodium sheet and diaphragm were assembled into a CR2025 button-type sodium ion battery in a glove box filled with high-purity argon. The electrolyte was 1 mol / L NaPF6 DME electrolyte, and the battery test system was used to test the charge and discharge performance and cycle stability of the sodium ion battery.
[0030] The method described in the present invention realizes the construction of high closed pore volume in lignin-based hard carbon, provides abundant filling sites for sodium ions in the closed pores of hard carbon, thereby realizing high platform capacity of hard carbon negative electrode of sodium ion battery.
[0031] The specific surface area of the high platform capacity lignin-based hard carbon material of the present invention is 2 to 8 m 2 g -1 , with abundant closed pores, and the closed pore volume is 0.3~0.5cm 3 g -1 The average size of the closed pores is 1-3 nm. The sodium ion half-cell was assembled in 1 mol / L NaPF6 DME electrolyte for testing. -1 When the display is 200 ~ 300mAh g -1 High platform capacity; hard carbon prepared from 153 mg zinc provides a capacity of up to 358 mAh g -1 .
[0032] The present invention aims to select lignin containing rich oxygen-containing functional groups and having a three-dimensional network structure to adsorb zinc ions. Zinc is uniformly dispersed in the lignin molecules at the atomic level. During the carbonization process, the three-dimensional network structure of lignin is used to inhibit the agglomeration growth of ZnO, and a highly dispersed ZnO template is generated to etch and form pores in the carbon material, thereby improving the specific surface area and uniformity of the pore structure of the carbon material; ZnO and C undergo carbon thermal reduction above 900°C to further activate and form pores in the carbon material, while the ZnO template is self-removed, and then the pores are closed at high temperature, thereby preparing a hard carbon negative electrode material with a high closed pore volume. This method not only uses environmentally friendly and low-cost lignin and zinc acetate as precursor materials, but also can realize one-step calcination to prepare a hard carbon material with a high closed pore volume, without the need to use additional acid, alkali and other solutions to remove the template. The hard carbon negative electrode prepared by this method not only has a rich closed pore structure, but also has good electrochemical properties.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0034] (1) The present invention utilizes lignin, which is abundant in source, low in cost and rich in oxygen-containing functional groups to provide active sites, as a carbon source. By adsorbing zinc ions to generate template pores, the open pores are transformed into closed pores at high temperature to prepare hard carbon negative electrode materials with smaller block size, large interlayer spacing and high closed pore volume, thereby improving the electrochemical performance of lignin-based hard carbon.
[0035] (2) The present invention adopts the method of lignin adsorbing zinc ions to prepare the precursor, and utilizes the rich oxygen-containing functional groups of lignin to adsorb and coordinate zinc ions. Zinc is dispersed in the lignin molecules at the atomic level. The uniform distribution of zinc ions and the in-situ generation of ZnO templates improve the specific surface area and uniformity of the pore structure of the carbon material.
[0036] (3) The present invention utilizes the three-dimensional network structure of lignin to effectively inhibit the agglomeration growth of ZnO, ensure the high dispersion of nano ZnO in the carbon matrix, and avoid the agglomeration of ZnO nanoparticles into large-sized particles, thereby avoiding the need for excessive etching of the carbon material to form a large pore structure that cannot be closed at high temperatures.
[0037] (3) The present invention uses lignin that can absorb zinc ions as a precursor, and the generated ZnO template performs two pore-forming effects on the carbon material. Specifically, during the heating process, the ZnO template etches the carbon material to form pores at 600-800°C and precipitates from the carbon matrix, and above 900°C, ZnO and carbon undergo a reduction reaction to further activate the carbon material to form pores. The two pore-forming effects produce a rich open-pore structure, which is beneficial to the increase of closed pore volume at high temperature.
[0038] (4) The hard carbon negative electrode prepared by the present invention not only increases the closed pore volume, but also has the advantage of a large interlayer spacing. The reduction reaction between ZnO nanoparticles and carbon not only provides an activation pore-forming effect for the carbon material, but also increases its interlayer spacing, providing a channel for the embedding of sodium ions in the hard carbon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the intermediate carbon product of the lignin-based hard carbon in Example 1 at 600°C (AL-Zn-600).
[0040] Figure 2 This is the SEM image of the intermediate carbon product of the lignin-based hard carbon in Example 1 at 800°C (AL-Zn-800).
[0041] Figure 3 This is the XRD pattern of the lignin-based hard carbon material (HC-Zn-1600) in Example 1.
[0042] Figure 4 This is the Raman graph of the lignin-based hard carbon material (HC-Zn-1600) in Example 1.
[0043] Figure 5 Example 1 Lignin-based hard carbon material (HC-Zn-1600) is used as a negative electrode for sodium ion batteries at 0.05 A·g -1 The second cycle charge and discharge curve under current density.
[0044] Figure 6 This is a graph showing the change in specific capacitance of the lignin-based hard carbon material (HC-Zn-1600) used as the negative electrode of a sodium ion battery in Example 1 as a function of current density.
[0045] Figure 7 This is a comparison chart of the electrochemical properties of hard carbon materials (HC-Zn-1600, HCS-Zn-1600 and HCB-Zn-1600) prepared in Example 1, Comparative Example 1 and Comparative Example 2 (different carbon sources).
[0046] Figure 8 Comparative Example 3: Lignin-based hard carbon material (HC-1600) is used as the negative electrode of sodium ion battery at 0.05 A·g -1 The second cycle charge and discharge curve under current density.
[0047] Fig. 9 This is a graph of comparative example 3, in which the lignin-based hard carbon material (HC-1600) is used as the negative electrode of a sodium ion battery, and its specific capacitance varies with current density.
[0048] Fig.10 Example 1 Lignin-based hard carbon material (HC-Zn-1600) is used as a negative electrode for sodium ion batteries at 1A·g-1 Cyclic curves at different current densities.
[0049] Fig.11 This is the SEM image of the lignin-based hard carbon precursor (AL-Zn) in Example 1.
[0050] Fig.12 This is the XRD pattern of the lignin-based hard carbon precursor (AL-Zn) in Example 1. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0052] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0053] Example 1
[0054] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of alkali lignin to the zinc acetate solution, stir in an oil bath at 70° C. for 4 h until uniformly mixed, and obtain lignin with an adsorption rate of 8%.
[0055] (2) Filter the suspension in step (1) to obtain lignin after adsorbing zinc ions, which is named AL-Zn.
[0056] (3) The AL-Zn obtained in step (2) is placed in a 90°C oven for 24 hours to obtain a dried AL-Zn precursor.
[0057] (4) The AL-Zn precursor in step (3) was heated to 1600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HC-Zn-1600.
[0058] The EDS and XRD of the AL-Zn precursor are shown in Figure 2. Fig.11 and Fig.12 shown. Fig.11 It can be observed that the zinc element is uniformly dispersed in the lignin, and no diffraction peaks of ZnO or Zn metal are observed from the XRD diagram of AL-Zn, indicating that after lignin adsorbs zinc salt, zinc is dispersed in the lignin molecules in the form of atoms.
[0059] The AL-Zn precursor was heated to 600℃ and 800℃ to obtain the intermediate carbon products of HC-Zn, which were named AL-Zn-600 and AL-Zn-800 respectively. The scanning tunneling microscope (SEM) images of AL-Zn-600 and AL-Zn-800 are shown in Figure 2. Figure 1 and Figure 2 shown. Figure 1 It can be observed that at 600 °C, ZnO begins to etch the carbon layer to form pores and gradually precipitates from the carbon matrix. At this time, the average size of ZnO is about 100 nm; Figure 2 It can be seen that when the temperature rises to 800°C, the ZnO template further etches the carbon layer to form pores, so that the carbon material is dispersed. The average size of ZnO is about 110nm, and there is no obvious agglomeration growth, which avoids excessive etching of the carbon material to form open pores that are difficult to close.
[0060] The X-ray diffraction (XRD) and Raman patterns of HC-Zn-1600 hard carbon anode are shown in Figure 3 and Figure 4 As shown, Figure 3 Two broad peaks appear near 23.9° and 43.6°, corresponding to the (002) and (100) crystal planes of the carbon material. According to the Bragg equation fitting calculation, the interlayer spacing of HC-Zn-1600 is 0.372nm, the La value of the carbon material is 5.45nm, and the Lc value is 1.08nm; after fitting calculation, the I D / I G The value is 1.75, which indicates that HC-Zn-1600 has a disordered carbon layer structure and a large interlayer spacing, which is beneficial to the transmission of sodium ions.
[0061] The prepared sodium ion battery electrode sheet was used as the working electrode, the sodium metal sheet as the counter electrode, and 1 mol / LNaPF6 (DME as the solvent) as the electrolyte to assemble a sodium ion half-cell, and the sodium ion storage performance of HC-Zn-1600 was tested, wherein DME was ethylene glycol dimethyl ether.
[0062] Figure 5 HC-Zn-1600 is used as the negative electrode of sodium ion battery at 0.05A·g -1 The second cycle charge and discharge curve under current density. At 0.05A·g -1 At a current density of 1.34 W, the platform capacity of HC-Zn-1600 in the second cycle is as high as 271 mAh g -1 , the platform capacity accounts for 75.7%.
[0063] Figure 6 This is a graph showing the change of specific capacitance with current density when HC-Zn-1600 is used as the negative electrode of sodium ion battery. -1At a current density of 358 mAh g -1 The specific capacity at 5A·g -1 At a current density of 87 mAh g -1 The specific capacity of HC-Zn-1600 is shown in Table 1. This indicates that HC-Zn-1600 has good rate performance when used as anode for sodium ion batteries.
[0064] Fig.10 HC-Zn-1600 is used as the negative electrode of sodium ion battery at 1A·g -1 Cycling performance diagram at a current density of . At this current density, HC-Zn-1600 has a capacity retention rate of 82% after 2000 cycles. This shows that HC-Zn-1600 has excellent cycling stability when used as a negative electrode for sodium ion batteries.
[0065] Example 2
[0066] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of alkali lignin to the zinc acetate solution, stir in an oil bath at 70° C. for 1 h until uniformly mixed, and obtain lignin with an adsorption rate of 6%.
[0067] (2) Filter the suspension in step (1) to obtain lignin after adsorbing zinc ions, which is named AL-Zn6.
[0068] (3) The AL-Zn6 obtained in step (2) is placed in a 90°C oven for 24 hours to obtain a dried AL-Zn6 precursor.
[0069] (4) The AL-Zn6 precursor in step (3) was heated to 1600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HC-Zn6-1600.
[0070] Example 3
[0071] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of alkali lignin to the zinc acetate solution, stir in an oil bath at 70° C. for 16 h until uniformly mixed, and obtain lignin with an adsorption rate of 10%.
[0072] (2) Filter the suspension in step (1) to obtain lignin after adsorbing zinc ions, which is named AL-Zn10.
[0073] (3) The AL-Zn10 obtained in step (2) is placed in a 90°C oven for 24 hours to obtain a dried AL-Zn10 precursor.
[0074] (4) The AL-Zn10 precursor in step (3) was heated to 1600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HC-Zn10-1600.
[0075] Example 4
[0076] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of alkali lignin to the zinc acetate solution, stir in an oil bath at 70° C. for 4 h until uniformly mixed, and obtain lignin with an adsorption rate of 8%.
[0077] (2) Filter the suspension in step (1) to obtain lignin after adsorbing zinc ions, which is named AL-Zn.
[0078] (3) The AL-Zn obtained in step (2) is placed in a 90°C oven for 24 hours to obtain a dried AL-Zn precursor.
[0079] (4) The AL-Zn precursor in step (3) was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HC-Zn-1400.
[0080] Example 5
[0081] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of alkali lignin to the zinc acetate solution, stir in an oil bath at 70° C. for 4 h until uniformly mixed, and obtain lignin with an adsorption rate of 8%.
[0082] (2) Filter the suspension in step (1) to obtain lignin after adsorbing zinc ions, which is named AL-Zn.
[0083] (3) The AL-Zn obtained in step (2) is placed in a 90°C oven for 24 hours to obtain a dried AL-Zn precursor.
[0084] (4) The AL-Zn precursor in step (3) was heated to 1200°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HC-Zn-1200.
[0085] Example 6
[0086] The difference between this embodiment and embodiment 1 is that the template source is zinc gluconate, and the alkali lignin-based hard carbon is obtained, which is named HC-ZnGlu-1600.
[0087] (1) Prepare 100 mL of 10 g / L zinc gluconate solution, add 6 g of alkali lignin to the zinc gluconate solution, and stir in an oil bath at 70 °C for 4 h until uniformly mixed.
[0088] (2) Filter the suspension in step (1) to obtain lignin after adsorbing zinc ions, which is named AL-ZnGlu.
[0089] (3) The AL-ZnGlu obtained in step (2) is placed in an oven at 90° C. for 24 hours to obtain a dried AL-ZnGlu precursor.
[0090] (4) The AL-ZnGlu precursor in step (3) was heated to 1600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HC-ZnGlu-1600.
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 1 is that the carbon source is starch, and starch-based hard carbon is obtained, which is named HCS-Zn-1600.
[0093] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of starch to the zinc acetate solution, and stir in an oil bath at 70 °C for 4 h until uniformly mixed.
[0094] (2) Filter the suspension in step (1) to obtain starch after adsorbing zinc ions, which is named St-Zn.
[0095] (3) The St-Zn obtained in step (2) is placed in an oven at 90°C for 24 hours to obtain a dried St-Zn precursor.
[0096] (4) The St-Zn precursor in step (3) was heated to 1600°C in a nitrogen atmosphere with a gas flow rate of 50 mL / min at a heating rate of 5°C / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HCS-Zn-1600.
[0097] Comparative Example 2
[0098] The difference between this comparative example and Example 1 is that the carbon source is bamboo powder, and the bamboo powder-based hard carbon is obtained, which is named HCB-Zn-1600.
[0099] (1) Prepare 100 mL of 10 g / L zinc acetate solution, add 6 g of bamboo powder to the zinc acetate solution, and stir in an oil bath at 70 °C for 4 h until uniformly mixed.
[0100] (2) Filter the suspension in step (1) to obtain bamboo powder after adsorbing zinc ions, which is named Ba-Zn.
[0101] (3) The Ba-Zn obtained in step (2) is placed in an oven at 90°C for 24 hours to obtain a dried Ba-Zn precursor.
[0102] (4) The Ba-Zn precursor in step (3) was heated to 1600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an in-situ zinc template-assisted alkali lignin-based hard carbon, named HCB-Zn-1600.
[0103] Comparative Example 3
[0104] This comparative example is about preparing hard charcoal by direct carbonization of lignin.
[0105] (1) Add 6 g of alkali lignin into 100 mL of aqueous solution and stir in an oil bath at 70 °C for 4 h until uniformly mixed.
[0106] (2) Filter the suspension in step (1) to obtain an alkali lignin material.
[0107] (3) placing the lignin obtained in step (2) in an oven at 90° C. for 24 hours to obtain dried alkali lignin.
[0108] (4) The alkali lignin in step (3) was pyrolyzed and carbonized at 1600°C for 4 h at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min to obtain an alkali lignin-based hard carbon named HC-1600.
[0109] The sodium ion battery electrode sheet prepared with HC-1600 was used as the working electrode, the sodium metal sheet as the counter electrode, and 1 mol / L NaPF6 (DME as the solvent) as the electrolyte to assemble a sodium ion half-cell, and the electrochemical performance of HC-1600 was tested.
[0110] Figure 8 The hard carbon material HC-1600 prepared in Comparative Example 3 was used as the negative electrode of the sodium ion battery. -1 The second cycle charge and discharge curve under current density. At 0.05A·g -1 At the current density of 1.37 W, the platform capacity of HC-1600 in the second cycle is only 230 mAh g -1 .
[0111] Fig. 9 This is a curve of the specific capacity of the negative electrode of the sodium ion battery used as Comparative Example 3 as a function of current density. -1At a current density of 306 mAh g -1 The specific capacity at 5A·g -1 At a current density of 46 mAh g -1 Specific capacity.
[0112] Figure 5 and Figure 8 It shows that in the absence of zinc salt as a template, the reversible capacity of the lignin-based hard carbon obtained by direct carbonization decreases. The difference between the specific capacity of HC-1600 and HC-Zn-1600 is mainly the platform capacity, which means that lignin adsorbs zinc salt as a template, and a large number of pores can be prepared on the lignin precursor during the carbonization process. A large number of pores contribute to the formation of closed pores during high-temperature carbonization, thereby increasing the platform capacity and specific capacity of lignin-based hard carbon.
[0113] Comparative Example 4
[0114] (1) Add 6 g of alkali lignin into 100 mL of aqueous solution and stir in an oil bath at 70 °C for 4 h until uniformly mixed.
[0115] (2) Filter the suspension in step (1) to obtain an alkali lignin material.
[0116] (3) placing the lignin obtained in step (2) in an oven at 90° C. for 24 hours to obtain dried alkali lignin.
[0117] (4) The alkali lignin in step (3) was pyrolyzed and carbonized at 1400°C for 4 h at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min to obtain an alkali lignin-based hard carbon named HC-1400.
[0118] Comparative Example 5
[0119] (1) Add 6 g of alkali lignin into 100 mL of aqueous solution and stir in an oil bath at 70 °C for 4 h until uniformly mixed.
[0120] (2) Filter the suspension in step (1) to obtain an alkali lignin material.
[0121] (3) placing the lignin obtained in step (2) in an oven at 90° C. for 24 hours to obtain dried alkali lignin.
[0122] (4) The alkali lignin in step (3) was pyrolyzed and carbonized at 1200°C for 4 h at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min to obtain an alkali lignin-based hard carbon named HC-1200.
[0123] Comparative Example 6
[0124] The difference between this comparative example and Example 1 is that alkali lignin and zinc acetate are physically mixed in the solid phase to prepare alkali lignin-based hard carbon, which is named HC-Zn-1600-S.
[0125] (1) 6 g of alkali lignin and 1 g of zinc acetate were solid-phase mixed and ground for 1 h until they were uniformly mixed.
[0126] (2) The mixture in step (1) was heated to 1600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a gas flow rate of 50 mL / min and pyrolyzed and carbonized for 4 h to obtain an alkali lignin-based hard carbon named HC-Zn-1600-S.
[0127] The reversible capacity and test current density in Table 1 are 50 mA g -1 The specific surface area material was obtained by fitting the nitrogen adsorption and desorption data using the BET model, and the closed pore diameter and closed pore volume were obtained by fitting the SAXS test results.
[0128] Table 1 shows the interlayer spacing, specific surface area, closed pore diameter, closed pore volume, platform capacity and specific capacity (test current density is 50 mA g) of the hard carbon samples prepared by the above embodiments and comparative examples. -1 ) comparison.
[0129] Table 1
[0130]
[0131] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high platform capacity lignin-based hard carbon material, characterized in that: The following steps are involved: (1) dispersing lignin in a zinc salt aqueous solution, heating and stirring, filtering, and drying to obtain a lignin-adsorbed zinc salt precursor; (2) In an inert gas atmosphere, the precursor is carbonized in one step to obtain a lignin-based hard carbon material.
2. The method for preparing a high platform capacity lignin-based hard carbon material according to claim 1, characterized in that: The mass ratio of the lignin to the adsorbed zinc salt in step (1) is 30:1 to 10:1; In the zinc salt aqueous solution of step (1), the zinc salt is at least one of zinc acetate and zinc gluconate.
3. A method for preparing a high platform capacity lignin-based hard carbon material according to claim 1 or 2, characterized in that: The mass ratio of lignin to zinc salt in step (1) is 12:1 to 4:1; The heating and stirring in step (1) is carried out at a temperature of 50 to 100° C. and for a time of 0.5 to 24 hours.
4. The method for preparing a high platform capacity lignin-based hard carbon material according to claim 3, characterized in that: The mass ratio of the lignin to the adsorbed zinc salt in step (1) is 17:1 to 10:1; The time of oil bath heating and stirring in step (1) is 1 to 16 hours.
5. The method for preparing a high platform capacity lignin-based hard carbon material according to claim 1 or 2, characterized in that: The temperature of the one-step carbonization in step (2) is 1200-1700° C. and the time is 1-4 hours; The heating rate of the one-step carbonization in step (2) is 1-30°C / min, and the flow rate of the inert gas is 2-100mL / min.
6. The method for preparing a high platform capacity lignin-based hard carbon material according to claim 5, characterized in that: The temperature of the one-step carbonization in step (2) is 1200-1600°C.
7. A method for preparing a high platform capacity lignin-based hard carbon material according to claim 1 or 2, characterized in that: The lignin in step (1) is at least one of alkali wood lignin, enzymatic lignin and lignin sulfonate; The mass concentration of the zinc salt aqueous solution in step (1) is 5 to 20 g / L.
8. The method for preparing a high platform capacity lignin-based hard carbon material according to claim 1 or 2, characterized in that: The inert gas in step (2) is at least one of nitrogen, argon and helium; The drying temperature in step (1) is 90° C. and the drying time is 24 hours.
9. A high-platform capacity lignin-based hard carbon material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the high platform capacity lignin-based hard carbon material according to claim 9 in sodium ion batteries.
Citation Information
Patent Citations
Preparation method of negative electrode material of sodium ion battery, negative electrode material and battery
CN118684227A
Lignin-based hard carbon / carbon nanotube composite material and preparation method and application thereof in negative electrode materials of lithium ion batteries
CN107959006A
Lignin porous carbon nanosheet as well as preparation method thereof and application in supercapacitor electrode material
CN109485029A
High-mesoporous-rate nitrogen and sulfur double-doped lignin-based carbon material as well as preparation and application thereof
CN116199206A
Hard carbon negative electrode material and preparation method thereof, negative electrode plate, sodium ion battery and electric equipment
CN117080437A
Cited By
Pre-activated-carbonized lignin-based hard carbon as well as preparation method and application thereof
CN120736520A
A pre-activated-carbonized lignin-based hard carbon, its preparation method and application
CN120736520B